Fundamentals and principles for engineering proteolytic activity - Craik, Charles (Henry Stewart Talks, 2007)
Protein engineering goals, Applications of engineered proteins, Strategies for engineering proteins, Specific examples of redesigned proteases to understand structure/function relationships, Engineered catalysis and molecular recognition in proteases
Reviewed at 2016/09/30